CORRELATION BETWEEN THE ABILITY OF USING ENGLISH COLLOCATION AND ACADEMIC ACHIEVEMENTS OF STUDENTS OF FACULTY OF TEACHER TRAINING AND EDUCATION UNIVERSITAS SRIWIJAYA - Hariswan Putera Jaya; Alhenri Wijaya; Dedi Kurniawan (Politeknik Negeri Sriwijaya, 2019)
This study is aimed at finding out the ability of students to use English collocation and its correlation with their academic achievements. The samples of this study are the 5th semester students of English education study program, UniversitasSriwijaya. Data were gathered by means of ability test using English collocation and academic achievements, GPA. The analysis results showed that there was a positive correlation between the ability of students to use English collocation and their academic achievements.